ADOPTION OF FARMERS IN THE IMPLEMENTATION OF TOMATO GOOD HANDLING PRACTICES (GHP) IN VILLAGE SENANING SUBDISTRICT - Afifah, Bunga Richa (Universitas Djuanda, 2020)
Tomato plants are vegetables that are easily damaged (parisable) so that requires the application of Good Handling Practices (GHP) which aims to reduce post-harvest yield loss. The purpose of this Final Assignment study is to increase farmers' knowledge about the application of tomato GHPs, namely treatment from harvest to market. This Final Project was carried out in the village of Senaning, Pemayung Sub-District, Batanghari Regency, Jambi Province from March to July 2020. The method used was descriptive method and multiple linear regression. Respondents were taken as many as 30 people who were determined deliberately (purposive sampling), namely farmers who are members of the tomato farmer group. The results showed that of 30 respondents at the level of farmer adoption, there were 17 knowledge persons in the low category (56.7%) and 13 moderate people (43.3%). Factors that influence the adoption of farmers in the application of GHP tomatoes are divided into 7 namely age, education, experience of farming, the role of extension workers, extension activities, availability of information and availability of facilities and infrastructure. From the analysis of variance analysis (Anova), it was found that all seven independent variables had a significant effect on the adoption of GHP tomato farmers (0.000> 0.05). Partially using the multiple linear regression formula, the results found that 6 independent variables, namely age (0.003), education (0.017), experience of farming (0.001), role of extension workers (0.029), extension activities (0.008), and availability of information (0.048) influence significant towards the adoption of farmers in the application of tomato GHP (Sig <0.05). While the availability of production facilities does not affect the adoption of farmers in the application of tomato GHP (0.119). The strategy taken to increase the adoption of farmers in the application of tomato GHP is by conducting counseling of tomato GHP and making a demonstration plot of tomato plants. After counseling there was a significant increase in the knowledge of farmers on tomato GHP with the T test sig (0,000).